Pelatihan Pembuatan Sabun Kertas dari Limbah Minyak Jelantah sebagai Solusi Alternatif Produk Ramah Lingkungan - Maulana, Ilham; Shapira, Shari Bella; Ismiati, Silfia; Ratiani, Syifa Intan (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Improper management of used cooking oil waste can cause environmental pollution and negatively impact public health. This community service aims to increase awareness and skills among SMK Tunas Bangsa students in utilizing used cooking oil waste as a raw material for environmentally friendly and economical hand soap production. The method applied is Participatory Action Research (PAR), actively involving students throughout the process, from understanding the waste impact, refining the used oil, to the practical making of paper soap. The results showed significant improvement in students’ knowledge and technical skills, along with high enthusiasm during the training. This activity successfully fostered environmental awareness and opened opportunities for recycling-based entrepreneurship. Main challenges such as limited time and equipment were identified for improvement in future programs. Overall, this community service effectively shaped environmental consciousness and practical skills in students as part of a sustainable solution.